Asterisk : the future of telephony - Meggelen, Jim Van (O'Reilly, 2005)
It may be a while before Internet telephony with VoIP (Voice over Internet Protocol) reaches critical mass, but there's already tremendous movement in that direction. A lot of organizations are not only attracted to VoIP's promise of cost savings, but its ability to move data, images, and voice traffic over the same connection. Think of it: a single Internet phone call can take information sharing to a whole new level. That's why many IT administrators and developers are actively looking to set up VoIP-based private telephone switching systems within the enterprise. The efficiency that network users can reach with it is almost mind-boggling. And cheap, if the system is built with open source software like Asterisk. There are commercial VoIP options out there, but many are expensive systems running old, complicated code on obsolete hardware. Asterisk runs on Linux and can interoperate with almost all standards-based telephony equipment. And you can program it to your liking. Asterisk's flexibility comes at a price, however: it's not a simple system to learn, and the documentation is lacking. Asterisk: The Future of Telephony solves that problem by offering a complete roadmap for installing, configuring, and integrating Asterisk with existing phone systems. Our guide walks you through a basic dial plan step by step, and gives you enough working knowledge to set up a simple but complete system. What you end up with is largely up to you. Asterisk embraces the concept of standards-compliance, but also gives you freedom to choose how to implement your system. Asterisk: The Future of Telephony outlines all the options, and shows you how to set up voicemail services, call conferencing, interactive voice response, call waiting, caller ID, and more. You'll also learn how Asterisk merges voice and data traffic seamlessly across disparate networks. And you won't need additional hardware. For interconnection with digital and analog telephone equipment, Asterisk supports a number of hardware devices. Ready for the future of telephony? We'll help you hook it up.